TENSES MASTER APPLICATION IN ENGLISH GRAMMAR LEARNING - Badroeni Badroeni; Sofhian Fazrin Nasrulloh; Yoyo Zakaria (English Review: Journal of English Education, 2020)
The background of this research is based on the urgency of mastering basic English grammar in supporting the understanding of advanced English grammar. Basic English grammar are tenses. Tenses are basic language formulas related to the simple construction of sentences. Tenses master application is designed based on need analysis which consists of functional needs and non-functional needs. The purposes of this study are to 1) identify the needs of grammar learning media according to teachers and students, 2) identify learning models that have been and are being carried out in schools, 3) know the principles of developing instructional media based on theoretical studies, identification of needs and analysis of existing instructional media, 4) design learning media based on the results of learning analysis, 5) design learning media, and 6) test application-based learning media tenses. The research method used was research and development. The stages of the R&D method in accordance with Borg and Gall theory are 1) conducting research and information gathering, 2) conducting planning, 3) developing initial forms of products, 4) conducting field tests and product revisions, 4) revising products, and 5) disseminating and implementing. The result indicated that the mean of pretest was 27.4 and the mean of posttest was 60.65. Hence, it can be concluded that tenses master application can enhance the students’ grammar competence and practice.